APPLYING COOPERATIVE INTEGRATED READING AND COMPOSITION TO IMPROVE READING COMPREHENSION AND WRITING ACHIEVEMENT - Wahyuni Sri; Diem Dahlan Chuzaimah; Ekawati Dian (Universitas Jambi, 2016)
The aim of this study was to find out whether or not; Cooperative Integrated Reading and Composition (CIRC) could improve the students’ reading comprehension and writing achievement. The population covered the whole eighth grade students of SMP 1 Pagaralam. 40 students were selected purposively as the sample and divided into two groups, experimental and control group each comprising of 20 students. During the research, the students in the experimental group were taught reading and writing by using CIRC. To check whether the application of CIRC could improve the students’ achievement, the students were given reading comprehension and writing test. The obtained data were analyzed by using paired sample t-test and independent t-test. Statistically, based on the result of paired sample t-test and independent t-test analyses, it strongly showed that there was significant improvement and difference in reading comprehension and writing achievement after the students were taught by using CIRC. Key words: Reading Comprehension, Writing Achievement, CIRC